Dari Aktualisasi Diri ke Transendensi Teosentris: Kritik atas Humanisme Eksistensial Abraham Maslow dan Rekonstruksi Teologi sebagai Basis Transformasi Sosial - Ratna Sari Nurmaulida; Fabela Sutriana Qudsi; S. Musdhalifah Indina Putri; Shabrina Malika Sweleh; Ali Hasan Siswanto (INDO PUBLISHING, 2026)
This article stems from the epistemological crisis in the integration of existential humanistic psychology with theology, particularly the thinking of Abraham Maslow, who tends to emphasize self-actualization within an anthropocentric framework. In the context of modern society, this approach faces limitations when faced with the need for social transformation based on transcendental values. The research gap lies in the absence of a conceptual formulation capable of systematically synthesizing self-actualization with the framework of Islamic theology and spirituality, especially in building a transformative theological society. This article uses an integrative theoretical approach that combines humanistic psychology, Islamic theology, and Sufism. The method used is qualitative research based on literature studies with critical, comparative analysis, and conceptual synthesis of primary and secondary literature. The main argument put forward is the need to reconstruct the concept of self-actualization towards theocentric transcendence, namely a paradigm that simultaneously integrates divine awareness, self-development, and social responsibility. The results of the study indicate that the integration of the concept of peak experience in humanistic psychology with the spiritual experience of Sufism can become a new epistemological foundation in understanding individual and social transformation. This article's scholarly contribution lies in proposing the concept of